Soft Rejection As A Politeness Strategy: A Sociolinguistic Analysis Of Gen Z’s Indirect Refusals In Whatsapp Communication - Pinta Ria Dewanti Zai; Ainur Rafika Azni; Nala Annisa Danin; Rahmadsyah Rangkuti (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
In sociolinguistic studies, politeness is understood as a linguistic strategy used to maintain social harmony, minimize conflict, and respect face needs in communicative interaction. This research examines soft rejection as a form of digital politeness strategy employed by Generation Z in WhatsApp communication. Grounded in Brown and Levinson’s (1987) Politeness Theory, this study analyzes how Gen Z applies both positive and negative politeness strategies to deliver indirect refusals politely while maintaining solidarity and personal autonomy. Using a descriptive qualitative method, the data were collected from screenshots of WhatsApp conversations containing examples of soft rejection among Gen Z users. The findings reveal that Gen Z frequently uses humor, emojis, and laughter markers such as “hehe” or “wkwk” as expressions of positive politeness, while phrases such as “sorry” or “maybe later” reflect negative politeness. These strategies indicate that digital politeness among Gen Z has evolved into a unique form of linguistic adaptation, where respect and familiarity are maintained through creative language use in digital communication.